2020
DOI: 10.1515/cclm-2019-1269
|View full text |Cite
|
Sign up to set email alerts
|

The “olfactory fingerprint”: can diagnostics be improved by combining canine and digital noses?

Abstract: AbstractA sniffer (detecting) dog is conventionally defined as an animal trained to use its olfactory perceptions for detecting a vast array of substances, mostly volatile organic compounds (VOCs), including those exceptionally or exclusively generated in humans bearing specific pathologies. Such an extraordinary sniffing performance translates into the capability of detecting compounds close to the femtomolar level, with performance comparable to that of current mass spectrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 71 publications
0
12
0
Order By: Relevance
“…A larger number of OSNs, particularly in species relying heavily on their sense of smell, may enhance further the detection of odorants. For instance, the human olfactory epithelium covers ∼3-4 cm 2 and contains approximately 5-6 million OSNs while in the case of dogs, the area of the olfactory epithelium is 18-150 cm 2 and contains 150-300 million OSNs (Lippi and Heaney, 2020).…”
Section: Sensitivity Of Photoreceptors and Olfactory Sensory Neuronsmentioning
confidence: 99%
“…A larger number of OSNs, particularly in species relying heavily on their sense of smell, may enhance further the detection of odorants. For instance, the human olfactory epithelium covers ∼3-4 cm 2 and contains approximately 5-6 million OSNs while in the case of dogs, the area of the olfactory epithelium is 18-150 cm 2 and contains 150-300 million OSNs (Lippi and Heaney, 2020).…”
Section: Sensitivity Of Photoreceptors and Olfactory Sensory Neuronsmentioning
confidence: 99%
“…Dogs can be also used in pet therapy. Recent studies are focused on their ability to detect pathological conditions such as cancers, diabetes, seizures, narcolepsy and migraine [38], as well as in case of a global health emergency such as the current COVID-19 pandemic [39]. For this reason, it is important to highlight that science can offer fundamental contribution to the K-9 field, in particular in forensic odorology where scientific evidence provided by dogs, further supported by traditional investigation techniques, can contribute to the successful outcome of a criminal proceeding.…”
Section: Admission Of Evidence Obtained By Dog Units At Trials: the I...mentioning
confidence: 99%
“…Bacterial Diseases: For the detection of bacterial diseases, dogs are expected to identify volatile metabolites, which are bacteria-specific fingerprints and produced during microbial replication (33). Two different training approaches have been conducted in the studies on the detection of bacterial infections by dogs.…”
Section: Detection Of Infectious Disease By Bio-detection Dogsmentioning
confidence: 99%
“…Although these specific VOCs can be identified by methods such as gas chromatography-mass spectrometry (GC-MS), potential use of this method as a diagnostic tool is limited because it is time consuming, expensive and it requires qualified operators (42). It has been reported that dogs' exceptional sniffing performance is comparable to the current mass spectrometry-based laboratory applications and is capable of detecting compounds close to the femtomolar level (33,62).…”
Section: Introductionmentioning
confidence: 99%